Byproduct-free geraniol glycosylation by whole-cell biotransformation with recombinant Escherichia coli - Priebe, Xenia (Biotechnol Lett, 2020)
OBJECTIVE: Geraniol, a fragrance of great importance in the consumer goods industry, can be glucosylated by the UDP-glucose-dependent glucosyltransferase VvGT14a from Vitis vinifera, yielding more stable geranyl glucoside. Escherichia coli expressing VvGT14a is a convenient whole-cell biocatalyst for this biotransformation due to its intrinsic capability for UDP-glucose regeneration. The low water solubility and high cytotoxicity of geraniol can be overcome in a biphasic system where the non-aqueous phase functions as an in situ substrate reservoir. However, the effect of different process variables on the biphasic whole-cell biotransformation is unknown. Thus, the goal of this study was to identify potential bottlenecks during biotransformation with in situ geraniol supply via isopropyl myristate as second non-aqueous phase. RESULTS: First, insufficient UDP-glucose supply could be ruled out by measurement of intracellular UDP-glucose concentrations. Instead, oxygen supply was determined as a bottleneck. Moreover, the formation of the byproduct geranyl acetate by chloramphenicol acetyltransferase (CAT) was identified as a constraint for high product yields. The use of a CAT-deficient whole-cell biocatalyst prevented the formation of geranyl acetate, and geranyl glucoside could be obtained with 100% selectivity during a biotransformation on L-scale. CONCLUSION: This study is the first to closely analyze the whole-cell biotransformation of geraniol with Escherichia coli expressing an UDP-glucose-dependent glucosyltransferase and can be used as an optimal starting point for the design of other glycosylation processes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10529-020-02993-z) contains supplementary material, which is available to authorized users.